Is the `athlete's heart` arrhythmogenic?: Implications for sudden cardiac death - Rowland, T. (Sports Medicine, 2011)
Whether the ventricular hypertrophic response to athletic training can predispose to fatal ventricular dysrhythmias via mechanisms similar to that of pathological hypertrophy is controversial. This review examines current information regarding the metabolic and electrophysiological differences between the myocardial hypertrophy of heart disease and that associated with athletic training. In animal studies, the biochemical and metabolic profile of physiological hypertrophy from exercise training can largely be differentiated from that of pathological hypertrophy, but it is not clear if the former might represent an early stage in the spectrum of the latter. Information as to whether the electrical remodelling of the athlete's heart mimics that of patients with heart disease, and therefore serves as a substrate for ventricular dysrhythmias, is conflicting. If ventricular remodelling associated with athletic training can trigger fatal dysrhythmias, such cases are extraordinarily rare and thereby impossible to investigate by any standard experimental approach. Greater insight into this issue may come from a better understanding of the electrical responses to both acute bouts of exercise and chronic training in young athletes.